Molecular mechanisms of photosynthesis - Blankenship, Robert E. (Blackwell Science, 2002)
Molecular mechanisms of photosynthesis stands as an ideal introduction to this subject. Robert Blankenship, a leading authority in photosynthesis research, offers a modern approach to photosynthesis in this accessible and well-illustrated text. The book provides a concise overview of the basic principles of energy storage and the history of the field, then progresses into more advanced topics such as electron transfer pathways, kinetics, genetic manipulations, and evolution. Throughout, Blankenship includes an interdisciplinary emphasis that makes this book appealing across fields.